2011
DOI: 10.1111/j.1552-6569.2010.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Diffusion Tensor Imaging for the Detection of Diffusion Abnormalities in the Trigeminal Nerves of Patients with Trigeminal Neuralgia Caused by Neurovascular Compression

Abstract: HR-DTI can detect an alteration in the relative FA values of affected trigeminal nerves and a correlation with atrophic changes in patients with NVC-induced TN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 23 publications
3
54
0
4
Order By: Relevance
“…But also regarding the non-affected side of patients with NVC-related TN, FA was significantly decreased in patients compared to that in healthy controls in this investigation, whereas ADC values did not differ significantly. These findings are in line with previous studies, indicating that FA might be more sensitive and detect more subtle anisotropic nerve changes compared to ADC [10,30].…”
Section: Discussionsupporting
confidence: 94%
“…But also regarding the non-affected side of patients with NVC-related TN, FA was significantly decreased in patients compared to that in healthy controls in this investigation, whereas ADC values did not differ significantly. These findings are in line with previous studies, indicating that FA might be more sensitive and detect more subtle anisotropic nerve changes compared to ADC [10,30].…”
Section: Discussionsupporting
confidence: 94%
“…Histological analysis from typical-TN patients showed that compressed trigeminal root specimens had axonopathies and axonal loss that could induce ectopic after-discharge and cross-excitation of neighboring fibers (Devor et al, 2002a,b). Those axonopathies are also evidenced by recent studies with diffusion tensor imaging (DTI) that demonstrated microstructural changes in the trigeminal roots of patients with trigeminal neuralgia (Fujiwara et al, 2010;Lutz et al, 2011). Furthermore, focal demyelination was demonstrated exactly at the REZ in cases of trigeminal neuralgia due to multiple sclerosis (Love et al, 2001).…”
mentioning
confidence: 72%
“…9,10,23,27 Here, no significant correlation between ADC values and any of the clinical, anatomical, and intraoperative findings was seen. This also included patients with a more severe, Grade III neurovascular compression.…”
Section: Fa Analysis But Not Adc Identifies Structural Alterationsmentioning
confidence: 90%